Cignana Archaeological Project (Sicilia): ceramiche di produzione africana dall’insediamento di età imperiale in contrada Viticchié - (:unkn) unknown (My University, 2017)
The rural settlement of Viticchié was found during the Cignana project, an archaeological survey carried out by the University of Palermo in collaboration with the Soprintendenza of Agrigento in the area around the Roman villa of Cignana (20km SE from Agrigento). Among over 200 new sites identified since 2007, Viticchié stands out from the others by the large number and the variety of pottery referable to a wide chronological range (3rd BC – 7th AD). In this paper, I will talk about the imports from Africa during the imperial age that represent the most common finds on this site. In many cases typology and fabrics allow us to distinguish different production and ateliers.
Keywords: African Research